Pesquisa clínica e experimental no Brasil oitocentista: circulação e controle do conhecimento em helmintologia médica Clinical and experimental research in nineteenth-century Brazil: the circulation and control of knowledge in medical helminthology - Flavio Coelho Edler (História, Ciências, Saúde: Manguinhos)
As contribuições de médicos brasileiros ao conhecimento sobre doenças causadas por vermes parasitas, na segunda metade do século XIX, produziram efeitos distintos em três comunidades epistêmicas: a anatomoclínica brasileira; a geografia médica francesa; e a emergente parasitologia médica. Admitindo a heterogeneidade dos regimes de legitimação dos fatos científicos e das práticas epistemológicas, descreve-se cartografia específica do conhecimento médico da época, revelando as linhas de força dos três campos disciplinares. O foco na circulação, no controle e na validação do conhecimento médico revela controvérsias e complicadas negociações entre distintas comunidades epistêmicas. The contributions of Brazilian physicians to knowledge of diseases caused by parasitic worms, during the second half of the nineteenth century, had distinct effects on three epistemic communities: Brazilian clinical anatomy, French medical geography, and the emerging field of medical parasitology. Accepting the heterogeneity of both the systems for legitimizing scientific facts and the epistemological practices observed by each discipline, the text provides a specific cartography of the period's medical knowledge, revealing the lines of force shaping the three disciplinary fields. The focus on the circulation, control and validation of medical knowledge reveals strong controversies and complicated negotiations between different epistemic communities.